What goes around, comes around: Reciprocal effects and double-sided moral hazard in the choice of brand licensing - Emanuele Bacchiega; Mariachiara Colucci; Marco Magnani (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2019)
Extending a brand beyond its original product category is a major strategy for long-term profitability. A brand owner can internalize the development of the extension product, or license the brand to an external partner in order to exploit the licensee's better capabilities and higher efficiency on the targeted market. Brand extension is characterized by the presence of the socalled reciprocal effect, whereby the effort exerted to develop and market the extension has a feedback effect - either positive or negative - on the value of the parent brand. Under licensing, this effect is an externality from the standpoint of the brand owner. The licensing relationship is characterized by double-sided moral hazard, requiring an incentivizing contract; the reciprocal effect adds a further element that should be governed by the contract. Indeed, a positive effect can boost the attractiveness of licensing relative to internal development, whereas a negative one can have the opposite effect. Drawing from extant literature, we build a game-theoretical model and show how reciprocal effect, (dis)similarity between the extension product and the parent brand, and (in)efficiency of the brand owner relative to the licensee in developing the extension shape the optimal licensing contract and affect the choice between internal development and licensing.
Keywords: L12; L24; 330; Brand Extension; Brand Licensing; Moral Hazard; Reciprocal Effect